Aktivitas Antibakteri Resin Pinus terhadap Staphylococcus aureus (Antimicrobial Activities of Pines Resin against Staphylococcus aureus) - Rita K Sari; Irmanida Batubara; Mardho Tillah; Dudi Tohir (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Previous research showed that n-hexane extract of Pinus oocarpa resin was the most potential extract among extracts of Pinus resin from Indonesia as antibacterial against Staphylococcus aureus. The purpose of this study were to separate the active antibacterial component of n-hexane P. oocarpa resin extract and characterize the functional groups of its most active fractions. The component were separated by silica gel column chromatography and detected by antibacterial bioautography method. Fraction F1 is the most active from 11 fractions. Furthermore, F1 separated further by preparative thin layer chromatography and sephadex LH-20 column chromatography. Three fractions (F1.1.1-F1.1.3) retrieved from the separation by sephadex LH-20 column. Furthermore F1.1.2 had the minimum inhibitory concentration and minimum bactericidal concentration of 125 and 250 µg ml-1 respectively against S. aureus by microdilution method. Characterization of fraction F1.1.2 using Fourier transformed infrared (FTIR) spectrophotometer shows that this fraction allegedly containing diterpenoid compounds.